Bal??le As A Ritual To Inherit Banggai Cultural Values - Samatan, Nuriyati; Wahyudin; Ariandi Putra; Robingah (Green Publisher, 2023)
This research aims to examine Baleele culture as a value inheritance ritual in Banggai culture. This research is qualitative, using an ethnographic approach with the following steps: [1] Determining the object of ethnographic research; [2] Identifying and determining the location of the cultural group; [3] Selecting the cultural theme of the cultural group; [4] Determining the type of ethnography; [5] Collecting information; [6] Writing research results. The result found that Baleele is a form of ritual communication carried out at a certain time, ahead of the